ELECTROSPUN COMPOSITE NANOFIBER POLYVINYLPYROLIDONE/CELLULOSE ACETATE LOADED WITH BANDOTAN LEAVES EXTRACT (AGERATUM CONYZOIDES) AS WOUND DRESSING APPLICATION - Latiffah, Efa
Indonesia is a tropical country in which various kinds of plants grow, which of course have many benefits for human life. Even wild plants or weeds can be used for example for traditional medicine. One of these plants is bandotan or babandotan. Bandotan plant has properties for wound healing, antibacterial, antiinflammatory, antioxidant, antiulcer, fever, and diarrhea. The parts of the bandotan plant that are often used are the roots and leaves. Herbal plants have natural antibiotics which are certainly safer for biomedical applications. The development of research on active compounds of herbal plants has also accompanied the development of other research such as wound dressings. The use of a wound dressing is very important in moist wound therapy, where it can provide an optimal environment for healing and protect the wound from bacterial infection. The form of wound dressing that has attracted much attention is nanofiber because it has many superior properties. Nanofibers have morphological similarities to the extracellular matrix (ECM), greater porosity, high surface area ratio, flexibility, permeability to oxygen, and can be a drug delivery medium. The most superior and widely used nanofiber fabrication technique is the electric spinner. The electric spinner can produce continuous nanofibers with very small fiber diameters and adjustable porosity. With the ease of combining chemicals in polymer solutions, the electric spinner can be a method for producing composite nanofibers from polymers and herbal plant extracts. This study aims to encapsulate EDB into polyvinyl pyrrolidone (PVP)/cellulose acetate (SA) matrix using the electrospinning technique as an antibacterial agent for wound dressing applications. Antibacterial activity of 20% (w/w) EDB solution had an inhibition zone against S. aureus bacteria was 9.3 mm and for P. aeruginosa bacteria was 7.4 cm. The KHM values are 1.25% and 5% (w/w) and the KBM values are 2.5% and 10% (w/w). The EDB was mixed with PVP/SA polymer as the next precursor solution. From the optimization of process parameters, the optimal voltage is 15 kV and the optimal flow rate is 1 ml/hour. Parameters of electrospinning of PVP/SA/EDB nanofibers used were flow rate of 1 ml/hour, the voltage of 15 kV, collection distance of 16 cm, and relative humidity of 50%. The addition of EDB to PVP/SA/EDB nanofibers resulted in pure fiber and no beads, but thin fibers were formed. Due to the instability of the jet when the EDB concentration is higher. Fiber diameter decreased with increasing EDB concentration, from 346.33 ± 74.39 nm for PVP/SA fiber to 144.82 ± 83.12 nm for EDB5. The value of k_v also varies from 0.21 to 0.57 which represents uniform to non-uniform fibers. This is related to the characteristic of the PVP/SA/EDB solution, where the viscosity and surface tension decrease with increasing EDB concentration, while the conductivity increases with increasing EDB. FTIR analysis showed that PVP/SA/EDB fiber had similarities with pure EDB spectrum, EDB was successfully encapsulated. There are phenolic, flavonoids, and saponins that cause antibacterial activity. Increasing the concentration of EDB will increase the antibacterial activity of nanofibers. The resulting nanofiber also has a pH=4 which can inhibit bacterial growth. Nanofibers PVP/SA/EDB have high sweling degree 785.656% which indicates the ability of the fiber to absorb wound fluid exudate and t's can accelerate the wound healing process. PVP/SA/EDB composite nanofibers have good performance to be applied as a wound dressing.